2015
DOI: 10.4111/kju.2015.56.8.546
|View full text |Cite
|
Sign up to set email alerts
|

Urologic robotic surgery in Korea: Past and present

Abstract: Since 2005 when the da Vinci surgical system was approved as a medical device by the Korean Ministry of Health and Welfare, 51 systems have been installed in 40 institutions as of May 2015. Although robotic surgery is not covered by the national health insurance service in Korea, it has been used in several urologic fields as a less invasive surgery. Since the first robotic-assisted laparoscopic radical prostatectomy in 2005, partial nephrectomy, radical cystectomy, pyeloplasty, and other urologic surgeries ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 44 publications
2
10
0
Order By: Relevance
“…Countering the possible limitations, our results are based on a nationwide, randomly selected population based cohort, thus generalizable to the entire Korean PC population. Considering that our estimated number of RARP cases is consistent with the recently published result [ 15 ], we believe that our operational definition for RARP appropriately represents an overall increasing trend of RARP in Korea. In addition, analysis of time trends over 10 years highlights changing patterns of primary treatment for PC in Korea.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Countering the possible limitations, our results are based on a nationwide, randomly selected population based cohort, thus generalizable to the entire Korean PC population. Considering that our estimated number of RARP cases is consistent with the recently published result [ 15 ], we believe that our operational definition for RARP appropriately represents an overall increasing trend of RARP in Korea. In addition, analysis of time trends over 10 years highlights changing patterns of primary treatment for PC in Korea.…”
Section: Discussionsupporting
confidence: 88%
“…We also assessed trends in surgery and primary ADT. Regarding surgical modalities, we found that use of RARP has increased since its introduction in 2005, and the number of cases showed a remarkable increase in 2008 because the installation of the da Vinci surgical system increased dramatically in 2008, consistent with a recent study [ 15 ] which reported an increasing trend of the total number of RARP on the basis of the data from Intuitive Surgical Korea Ltd. (Seoul, Korea). As such, RARP use recently exceeded conventional RP.…”
Section: Discussionsupporting
confidence: 87%
“…Searching in the literature, the most recurrent issues concerning surgical robots and insurance are about the coverage of specific surgical interventions by the national health insurance service [39,40] and about the reduced health insurance costs resulting from robotic assisted surgery [41]. These issues are relevant also for other medical applications of robots, such as prosthetic devices, as reported by [2].…”
Section: Service Robotsmentioning
confidence: 99%
“…Since robotic surgery had been introduced to the surgical field in 1999 [53], robot-assisted laparoscopic radical prostatectomy (RALP) has been widely performed to treat prostatic cancer [54]. Most prostatectomies are currently performed by robot-assisted surgery [55].…”
Section: Prostatectomymentioning
confidence: 99%